Knowledge, attitude and practice relating to food supplement intake among Universiti Teknologi MARA (UiTM) Terengganu students / Nur Athirah Muhamad Sobri dan Nurul Natasha Azira Shahrudin - Muhamad Sobri, Nur Athirah; Shahrudin, Nurul Natasha Azira (Faculty of Hotel and Tourism, 2017)
The research study paper is about determine the level knowledge, attitude and practices relating to food supplement intake among Universiti Teknologi Mara (UiTM) Terengganu students. Food supplement which is also known as dietary supplements are popular in so many countries including Malaysia. The data is available by the target population which is university students on their food supplement intake. The result of the collecting data is obtained by 186 respondents and captured by using a set of questionnaire with four sections. Since the university students has variety habits, characteristics or lifestyle, their intake of food supplement may differ from the general population. The result reveal that the students have a lot of knowledge about the food supplement intake and only a few of them are not sure with the answer. They also have a good attitude and well practices towards food supplement intake. Food supplement also may be used in context of healthy lifestyle or as compensate for unhealthy lifestyle. The design of this research study is quantitative approach. This study investigate the effects of three independent variables which are knowledge, attitudes, practice and dependent variable which is food supplement intake.